A dinuclear cobalt cluster as electrocatalyst for oxygen reduction reaction. Issue 72 (23rd December 2019) - Li, Yun-Wu; Zhang, Wen-Jie; Li, Chun-Xia; Gu, Lin; Du, Hong-Mei; Ma, Hui-Yan; Wang, Su-Na; Zhao, Jin-Sheng
Abstract : A Pt-free dinuclear CoII2 cluster was selected to research its ORR catalytic activities. The CoII2 possesses defined crystal structure and displays a nice ORR electrocatalytic performance by a nearly 4-electrons reduction pathway. Abstract : Dinuclear metal clusters as metalloenzymes execute efficient catalytic activities in biological systems. Enlightened by this, a dinuclear CoII2 cluster was selected to survey its ORR (Oxygen Reduction Reaction) catalytic activities. The crystalline CoII2 possesses defined structure and potential catalytic active centers of CoN4 O2 sites, which was identified by X-ray single crystal diffraction, Raman and XPS. The appropriate supramolecular porosity combining abundant pyridinic-N and triazole-N sites of CoII2 catalyst synergistically benefit the ORR performance. As a result, this non-noble metal catalyst presents a nice ORR electrocatalytic activity and abides by a nearly 4-electron reduction pathway. Thus, this unpyrolyzed crystalline catalyst clearly provide precise active sites and the whole defined structural information, which can help researcher to design and fabricate efficient ORR catalysts to improve their activities. Considering the visible crystal structure, a single cobalt center-mediated catalytic mechanism was also proposed to elucidate the ORR process.